Respuesta :

leena

Hi there!

[tex]\sqrt{\frac{1-cosA}{1+cosA}} =[/tex]

We can begin by multiplying by its conjugate:

[tex]\sqrt{\frac{1-cosA}{1+cosA}} * \sqrt{\frac{1+cosA}{1+cosA}} = \\\\\sqrt{\frac{(1-cosA)(1 + cosA)}{(1+cosA)(1 + cosA)}} =[/tex]

Simplify using the identity:

[tex]1 - cos^2A = sin^2A[/tex]

[tex]\sqrt{\frac{(1-cos^2A)}{(1+cosA)^2}} =\\\\\sqrt{\frac{(sin^2A)}{(1+cosA)^2}} =[/tex]

Take the square root of the expression:

[tex]{\frac{sinA}{1+cosA} =[/tex]

Multiply again by the conjugate to get a SINGLE term in the denominator:

[tex]{\frac{sinA}{1+cosA} * {\frac{1-cosA}{1-cosA} =\\[/tex]

Simplify:

[tex]{\frac{sinA(1-cosA)}{1-cos^2A} =[/tex]

Use the above trig identity one more:

[tex]{\frac{sinA(1-cosA)}{sin^2A} =[/tex]

Cancel out sinA:

[tex]{\frac{(1-cosA)}{sinA} =[/tex]

Split the fraction into two:

[tex]{\frac{1}{sinA} - \frac{cosA}{sinA} =[/tex]

Recall:

[tex]1/sinA = cscA\\\\cosA/sinA = cotA[/tex]

Simplify:

[tex]\frac{1}{sinA} + \frac{cosA}{sinA} = \boxed{cscA - cotA}[/tex]